Transformation of Fast Food Culture in Rural Adolescents: Evidence from a study in Prayagraj, Uttar Pradesh - Keshari, Priya; Giri, Deeksha (Indian Journal of Community Health, 2024)
Socio cultural context is changing in rural India. This may lead to establishment of fast food culture in rural areas as well. Objectives: To find out extent, pattern and associates of knowledge, opinion and consumption of fast food by rural adolescents. Materials and Methods: This community based cross sectional study was conducted on 213 adolescents selected by multistage sampling procedure from rural Prayagraj. Each subject was interviewed about socio-demographic characteristics, knowledge, opinion, and consumption of fast foods with the help of predesigned and pretested proforma. Analysis of data was done through SPSS and for finding out associates chi square test was applied. Results: Majority of subjects were aware about fast food and 84.0% consumed it in the previous month. There existed significant association of opinion of subjects regarding fast food fulfills hunger with type of family, social class of subjects (P<0.01) whereas, opinion of subjects "Feel energetic after eating fast food" was significantly associated with their gender, type of family and social class (P<0.05). Consumption of fast food was significantly more in subjects from nuclear family and higher SES (P<0.01). Conclusion: Socio Economic gradient prevailed in the expression of the opinions “the fast food fulfill hunger” and “Feel energetic after eating fast food” as well as consumption of fast food by subjects.